Using Index Card Match to Improve Twelfth-Grade Cadets’ Reading Comprehension: A Classroom Action Research at Poltekpel Malahayati Aceh - Piping Rahadianto; Yuli Pera Fitria; Yusrah (Journal of Applied Linguistics, 2026)
Students’ limited interest in reading English texts is often associated with low levels of reading comprehension. This study aimed to improve students’ reading comprehension through the implementation of the Index Card Match strategy in an English classroom. The research adopted a classroom action research design based on the Kemmis and McTaggart model, consisting of two cycles, each comprising planning, action, observation, and reflection stages. Data were collected through observation sheets, field notes, interviews, reading comprehension tests, and student questionnaires. The quantitative findings demonstrated a progressive improvement in students’ reading comprehension across the research cycles. The proportion of students meeting the predetermined achievement criteria increased from 44% in the pre-test to 70% in Cycle I and further to 91% in Cycle II. Qualitative data supported these results, indicating increased student engagement, enjoyment, and motivation during reading activities. The findings suggest that the Index Card Match strategy is effective in enhancing students’ reading comprehension and creating a more interactive learning environment. Therefore, it is recommended that English teachers consider integrating this strategy into reading instruction, while future studies may explore its application in different educational contexts or through alternative research designs. Keywords : Index Card Match; Reading Comprehension; Class Action Research